The First Steps to Building Research Collaborative Using Strength-Based Assessments and GIS Maps with a Sample of Community-Based Organizations in the Bronx, NY - María Isabel Roldós; Jaye Jones; Jocelyn Rajaballey (Health Equity)
Introduction: Community-based participatory research (CBPR) is one of the most effective strategies for conceptualizing, developing, and executing programs or interventions that address health disparities in community settings. The City University of New York (CUNY)'s Institute for Health Equity (CIHE) focuses on the social determinants that affect the physical and mental health of New York City's poor and underserved. Methods: This study utilized a modified Strengths, Weaknesses, Opportunities, and Threats (SWOT) tool as a strength-based assessment (SBA) to evaluate community-based organization (CBO)'s Areas for Growth (SWOT-SBA). This approach was used to identify CBOs' strengths, prospects, and priorities to address the Bronx's health disparities. Furthermore, this study collected descriptive information on CBO's catchment areas, services provided, and population served to create interactive and static maps and contingency tables using the Arch-GIS software. Results: This study was the first step to building CIHE Healthy-Bronx Research Collaborative to address the Bronx's health disparities. The results indicate that Hunts Point and Longwood Community Districts are the most served by CBOs. The SWOT-SBA suggests that CBOs' engagement through “appreciative inquiry” to conduct a CBPR has the most promise for a successful partnership between CBOs, research partners, and local stakeholders. Conclusion: This analysis suggests that CBOs center their resources to function as a leader in the Bronx and have identified the need to expand services during the pandemic. Findings from this study suggest that CBOs want to collaborate in CBPR initiatives.